HAAK, Jan Friedrich Wilhelm Inventory of documents - HAAK, Jan Friedrich Wilhelm (ARCA, 2018)
Private papers of J.F.W. Haak, National Party MP Bellville-Parow [1953-1955]. Bellville [1958-1970], Minister of Planning [1964-1967], Mines [1964-1967], Economic Affairs [1967-1970], Member of the President's Council [1987-1988]
COVERAGE 1941,1962-1970; 134 Files; 5,89 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 10
Keywords: HAAK, Jan Friedrich Wilhelm; Inventories; Politicians; National Party